(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2018)
The issue of financial exclusion has been the topic of scientific research for decades now. Each and every individual may become excluded with respect to an array of criteria, such as for instance educational background, income level, financial status, nationality or even a way of living. This means they are not allowed to perform certain social activities, even though they are both able and willing to undertake them. This unfavourable condition is usually caused by other people’s reluctance. The article addresses the issues of the perception of financial exclusion generation 55+ Poles by providing a survey’s outcome. Firstly, the awareness of financial exclusion problem among young people is presented. Secondly, the causes of the phenomenon are elaborated on, as well as types of individuals potentially endangered of such exclusion. Finally, the outcome of research is provided in terms of the evaluation of the phenomenon’s range and identification of people in charge of counteracting it.